2018
DOI: 10.1002/hbm.24187
|View full text |Cite
|
Sign up to set email alerts
|

Novel in silico multivariate mapping of intrinsic and anticorrelated connectivity to neurocognitive functional maps supports the maturational hypothesis of ADHD

Abstract: From childhood to adolescence, strengthened coupling in frontal, striatal and parieto-temporal regions associated with cognitive control, and increased anticorrelation between task-positive and task-negative circuits, subserve the reshaping of behavior. ADHD is a common condition peaking in adolescence and regressing in adulthood, with a wide variety of cognitive control deficits. Alternate hypotheses of ADHD emphasize lagging circuitry refinement versus categorical differences in network function. However, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…For example, in autism a hypothesis has been advanced that male sex may confer vulnerability, or female sex protective effects, operating at the genetic and/or neural levels. An interesting comparison can be made with our prior work in ADHD, a developmental disorder with a much higher reported incidence in males, where we surveyed a similar set of cognitive control functions and found that the neurocognitive footprint across these functions was much larger in youth with ADHD vs. neurotypical youth (de Lacy et al, 2018). More broadly, our results suggest that sex-related differences in cognitive performance may have intrinsic neural correlates.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, in autism a hypothesis has been advanced that male sex may confer vulnerability, or female sex protective effects, operating at the genetic and/or neural levels. An interesting comparison can be made with our prior work in ADHD, a developmental disorder with a much higher reported incidence in males, where we surveyed a similar set of cognitive control functions and found that the neurocognitive footprint across these functions was much larger in youth with ADHD vs. neurotypical youth (de Lacy et al, 2018). More broadly, our results suggest that sex-related differences in cognitive performance may have intrinsic neural correlates.…”
Section: Discussionmentioning
confidence: 94%
“…In this final step, we used the output of the multivariate analysis (see Statistical Analysis to Identify Sex-Related Effects in IN Spatial Maps) which identified significant sex-related effects in each IN in each model as the input to a mapping process where we mapped effects of sex in each IN to neurocognitive functional maps using a method which we recently developed and published (de Lacy et al, 2018). The aim of this analysis was to identify and compare the cognitive ‘footprint’ of sex-related differences in IN function across 16 cognitive functions and see how this varied between sexes, cognitive functions and 8-, 24-, and 51-network models of brain function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant imaging studies have reported brain structural and functional differences between patients with ADHD and HCs, both in childhood and adulthood. Many functional magnetic resonance imaging (fMRI) findings heavily support that ADHD involves a distributed pattern of brain alterations 3,4 . According to Rubia et al, functional abnormalities in fronto-cortical and fronto-subcortical networks are core deficits in both children and adults with ADHD 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Neural impairment is associated with many profound complex issues. For example, the patients with ADHD tend to have the response delayed in many aspects such as in the development of neurological organization and neuroplasticity (Van Doren et al, 2017), network analysis and brain development (de Lacy et al, 2018), cognitive function and motor control integration (Leisman et al, 2014), synergies and motor primitives, retained primitive reflexes (Konicarova et al, 2013) and many other areas that all impinge on which is necessary to build models to help understanding the nature of neurodevelopmental disorders. As ADHD symptoms change over time, linguistic and locomotor maturation cannot reach social maturity at any developmental stage (Giertuga et al, 2017).…”
mentioning
confidence: 99%